2020
DOI: 10.1101/2020.04.13.039669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The hexosamine biosynthesis pathway is a targetable liability in lung cancers with concurrent KRAS and LKB1 mutations

Abstract: In non–small cell lung cancer (NSCLC), concurrent mutations in the oncogene KRAS and the tumor suppressor STK11 encoding the kinase LKB1 result in aggressive tumors prone to metastasis but with liabilities arising from reprogrammed metabolism. We previously demonstrated perturbed nitrogen metabolism and addiction to an unconventional pathway of pyrimidine synthesis in KRAS/LKB1 co-mutant (KL) cancer cells. To gain broader insight into metabolic reprogramming in NSCLC, we analyzed tumor metabolomes in a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…KRAS/LKB1 mutant NSCLC depends on GFPT2 and associated pathway components. Azaserine reduces KRAS/LKB1 comutant cell viability (104). Oncogenic KRAS and LKB1 deletion predict aggressive cancer in mice and humans.…”
Section: Kras Mutationsmentioning
confidence: 99%
“…KRAS/LKB1 mutant NSCLC depends on GFPT2 and associated pathway components. Azaserine reduces KRAS/LKB1 comutant cell viability (104). Oncogenic KRAS and LKB1 deletion predict aggressive cancer in mice and humans.…”
Section: Kras Mutationsmentioning
confidence: 99%
“…PTMs have gained significant interest in recent omics studies as they directly modulate numerous cancer hallmarks including cell cycle progression, migration and metabolism (12)(13)(14)(15). Previous work showed that metabolic reprogramming toward the hexosamine biosynthesis pathway (HBP), an understudied glucose pathway leading to glycosylation, is associated with poor survival in the lung adenocarcinoma (LUAD) (16,17). The authors reported that this metabolic switch happens earliest in CAFs compared to the malignant cells across tumor compartments (fibroblasts, cancer, immune and endothelial cells).…”
Section: Introductionmentioning
confidence: 99%